2020
DOI: 10.1139/cjas-2019-0088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of follicle-stimulating hormone beta subunit and nuclear receptor coactivator 1 gene polymorphisms and expressions on pink-eyed white mink reproductive traits

Abstract: The present study was designed to investigate comparative expression of follicle-stimulating hormone beta subunit (FSHβ) and nuclear receptor coactivator 1 (NCOA1) genes by real-time PCR (RT-PCR), using Polymerase Chain Reaction-Single-Strand Conformation Polymorphism (PCR-SSCP) methods to investigate the effects of gene polymorphisms on reproductive traits including total number of kits born (TNB) and number of born alive (NBA) in pink eyed white mink. Four SNPs were identified in the FSHβ and NCOA1 genes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…The FSHβ protein can freely diffuse into prokaryotic cells after its expression. In the prediction of subcellular localization, our results indicated that FSHβ protein was also expressed in the nucleus (Liu et al 2020;Tian et al 2023). In addition, further prediction using TMHMM confirmed that there was no obvious transmembrane domain and signal peptide distribution in the FSHβ protein (Palmerini et al 2016;Niu et al 2019).…”
Section: Discussionmentioning
confidence: 62%
“…The FSHβ protein can freely diffuse into prokaryotic cells after its expression. In the prediction of subcellular localization, our results indicated that FSHβ protein was also expressed in the nucleus (Liu et al 2020;Tian et al 2023). In addition, further prediction using TMHMM confirmed that there was no obvious transmembrane domain and signal peptide distribution in the FSHβ protein (Palmerini et al 2016;Niu et al 2019).…”
Section: Discussionmentioning
confidence: 62%